2017
DOI: 10.18178/joaat.4.1.87-91
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Carotenoids, Phenolic Compounds and Antioxidant Capacity of Extracts from Gac Peel as Affected by Different Solvents and Extraction Conditions

Abstract:  Abstract-Gac fruit (Momordica cochinchinensis Spreng.) is a rich source of bioactive compounds especially carotenoids. Currently, only the aril of the Gac fruit is processed and the peel is discarded although it contains high levels of carotenoids and phenolic compounds, which could be extracted for commercial use. In the present study, solvent type, ratio of solvent to material, extraction time and temperature were investigated for the extraction yields of carotenoids and phenolic compounds, the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
2
4
0
1
Order By: Relevance
“…The result was consistent with a previous study that the total soluble solid of Roselle tea extracts reached a maximum after brewing for 40 min [27]. When the extracting time exceeded 40 min, the yield of instant sweet tea powders decreased, which may be associated with the degradation of bioactive compounds in sweet tea [28].…”
Section: Discussionsupporting
confidence: 92%
“…The result was consistent with a previous study that the total soluble solid of Roselle tea extracts reached a maximum after brewing for 40 min [27]. When the extracting time exceeded 40 min, the yield of instant sweet tea powders decreased, which may be associated with the degradation of bioactive compounds in sweet tea [28].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with our previous studies, which showed that β-carotene, lycopene and lutein contributed to approximately 90% of total carotenoid content in the peel of Gac fruit [6,7]. Ethyl acetate was also found as the most suitable solvent for a simultaneous extraction of those principal carotenoids from Gac peel compared to other solvents such as hexane, acetone and ethanol [26]. Previous studies on biological activities of Gac fruit showed that carotenoids from this fruit possess a variety of beneficial effects to human health.…”
Section: Carotenoid Composition Of the Extract Obtained Under Optimalsupporting
confidence: 92%
“…This difference may be due to the additional release of other bioactive compounds from Gac peel, which also contributed to the antioxidant capacity into the liquid phase at the extended time. Kubola and Siriamornpun (2011) [5] reported that in addition to the high levels of carotenoids, Gac peel also contains significant levels of phenolic acids and flavonoids, which required a longer extraction time to reach their highest extraction yield compared to the time to achieve the highest carotenoid yield from Gac peel [26].…”
Section: Effects Of Extraction Conditions On Antioxidant Capacity Of mentioning
confidence: 99%
“…Our studies on the conventional extraction of bioactive compounds from Gac peel showed that carotenoids and antioxidant capacity from the peel can be efficiently extracted using organic solvents (Chuyen, Roach, Golding, Parks, & Nguyen, 2017c;Chuyen, Tran, et al, 2017). However, conventional methods require large volumes of solvents, high energy use and long extraction times for an efficient extraction of bioactive compounds.…”
mentioning
confidence: 99%